The way ahead: adaptive medical standards to optimize commercial space traveler health, safety and performance - Sobel, Annette Louise; Orford, Robert; Klingenberger, Karen (Frontiers in Space Technologies, 2023)
The promise of space travel opens a new era of opportunity for consideration of space medical standards, health screening, maintenance, and even environmental threat mitigation. There is a significant gap in scientific knowledge between previously well-established aeromedical standards for suborbital, orbital and beyond present a significant gap in scientific knowledge and mission-specific physiologic responses to extended duration activities. This paper will review the current and evolving standards and examine gaps and shortfalls which must be addressed to ensure space traveler safety and security. [1] In addition, we will address the international, cultural, and educational challenges of which potential space travelers and their health care providers must be aware, and will present an approach to systematically addressing these challenges.